2012
DOI: 10.1098/rstb.2012.0001
|View full text |Cite
|
Sign up to set email alerts
|

The conservation physiology of seed dispersal

Abstract: At a time when plant species are experiencing increasing challenges from climate change, land-use change, harvesting and invasive species, dispersal has become a very important aspect of plant conservation. Seed dispersal by animals is particularly important because some animals disperse seeds to suitable sites in a directed fashion. Our review has two aims: (i) to highlight the various ways plant dispersal by animals can be affected by current anthropogenic change and (ii) to show the important role of plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 74 publications
0
50
0
Order By: Relevance
“…Physiological tools have previously proven successful in addressing conservation issues related to both plants and animals. Pywell et al (2003) used physiological traits to assess the performance of plants in ecological restoration, Ruxton and Schaefer (2012) described how plant and animal physiology affects seed dispersal interactions and Tingvold et al (2013) showed how African elephants (Loxodonta africana) have lower stress hormone levels inside protected parks compared to individuals outside. Conservation physiology can thus be used to understand and potentially solve a wide variety of conservation related problems.…”
Section: Conservation Physiologymentioning
confidence: 99%
“…Physiological tools have previously proven successful in addressing conservation issues related to both plants and animals. Pywell et al (2003) used physiological traits to assess the performance of plants in ecological restoration, Ruxton and Schaefer (2012) described how plant and animal physiology affects seed dispersal interactions and Tingvold et al (2013) showed how African elephants (Loxodonta africana) have lower stress hormone levels inside protected parks compared to individuals outside. Conservation physiology can thus be used to understand and potentially solve a wide variety of conservation related problems.…”
Section: Conservation Physiologymentioning
confidence: 99%
“…These interactions may be nested within the effect of abiotic drivers as in the example above where energetic needs for thermoregulation change in different environmental contexts. Nutrition, with respect to both energetic and macronutrient requirements, in particular determines interactions between organisms [32,33]. At a quantitative level, density of prey will determine predator numbers [34], but this relationship will change with environmentally driven changes in energy requirements, such as for thermoregulation.…”
Section: Ecological Success Is Coupled To Environmental Conditions VImentioning
confidence: 99%
“…For example, temperature affects the relative macronutrient requirements in trout, and fish at warm temperatures require relatively more protein than at cooler temperatures [35]. As a result, foraging behaviour must be adjusted to meet intake targets, and predation pressures shift to different prey species, potentially leading to a change in community structure and interactions [33].…”
Section: Ecological Success Is Coupled To Environmental Conditions VImentioning
confidence: 99%
“…These impacts on migrants may also have ecological ramifications at community and ecosystem scales, because migratory birds provide many ecosystem functions and services, such as pest control, assistance in dispersal of other organisms, pollination and nutrient cycling [7][8][9]. There is also increasing interest in how migratory birds may affect the abundance and distribution of diseases that threaten humans, such as highly pathogenic avian influenza virus H5N1 originating in Southeast Asia, and West Nile virus in the Americas [10].…”
Section: Introductionmentioning
confidence: 99%